Prevalence of Self-medication with Antibiotics amongst Clients Referred to Outpatient University Dental Clinics in Iranian Population: A Questionnaire-based Study - Emad, Sara; Abedi, Shadi; Dehghani, Zahra; Ghahramani, Yasamin (Iranian Endodontic Journal, 2020)
Introduction: Self-medication with antibiotics may increase the risk of inappropriate use and development of antibiotic-resistant bacteria. The aim of this study was to determine the prevalence of self-medication with antibiotics amongst dental outpatients in Iranian population. Methods and Materials: One thousand and two hundred of dentistry patients, who were referred to dental school clinics in ten major provinces of Iran, participated in this study. A valid self-administered questionnaire regarding self-medication with antibiotics in case of dental pain was used to collect data. Data were analysed using descriptive statistics and Logistic regression analysis. Results: In our study population, the prevalence of self-medication was 42.6%. Amongst the Iranian cities, the highest prevalence of self-medication with antibiotics belonged to the city of Bandar Abbas (64%) and the lowest was seen in the city of Kerman (27.3%). Men were more likely to take antibiotics. Amoxicillin was the mostly used antibiotic. Severe pain, previous self-medications and high costs of dental visits were the most common reasons for self-medication with antibiotics in the investigated population. In addition, the present study showed that marriage, acceptable financial status and high level of education could decrease self-medication with antibiotics. Conclusions: In the current investigation, an alarming fact was that self-medication for dental problems seemed very common amongst the studied population. One of its most important consequences was bacterial resistance. Therefore, there should be plans to promote and prioritize public health awareness and encourage general public’s motivation to reduce the practice of self-medication. Keywords: Antibiotics; Dental Clinics; Prevalence; Self-medication